Unruh Entropy of a Schwarzschild Black Hole - Maksym Teslyk; Olena Teslyk; Larissa Bravina; Evgeny Zabrodin (Particles, 2023)
The entropy produced by Unruh radiation is estimated and compared to the entropy of a Schwarzschild black hole. We simulate a spherical system of mass M by a set of Unruh horizons and estimate the total entropy of the outgoing radiation. Dependence on the mass and spin of the emitted particles is taken into account. The obtained results can be easily extended to any other intrinsic degrees of freedom of outgoing particles. The ratio of Unruh entropy to the Schwarzschild black hole entropy is derived in exact analytical form. For large black holes, this ratio exhibits high susceptibility to quantum numbers, e.g., spin s, of emitted quanta and varies from 0% for <semantics>s=0</semantics> to 19.0% for <semantics>s=5/2</semantics>.